Lower Extremity Peripheral Arterial Disease Is an Independent Predictor of Coronary Heart Disease and Stroke Risks in Patients with Type 2 Diabetes Mellitus in China. (8th May 2017) - Pang, Xiao-Hong; Han, Jue; Ye, Wan-Lan; Sun, Xue; Ding, Yue; Huang, Wen-Juan; Zhao, Yi-Ming; Lou, Han-Yu; Shan, Li-Zhen; Kang, Ying-Xiu; Song, Xiao-Xiao; Zhang, Song-Zhao; et al.
Abstract : We aimed to determine the relationship between lower extremity peripheral arterial disease (PAD), 10-year coronary heart disease (CHD), and stroke risks in patients with type 2 diabetes (T2DM) using the UKPDS risk engine. We enrolled 1178 hospitalized T2DM patients. The patients were divided into a lower extremity PAD group (ankle-brachial i n d e x ≤ 0.9 or >1.4; 88 patients, 7.5%) and a non-PAD group (ankle-brachial i n d e x > 0.9 and ≤1.4; 1090 patients, 92.5%). Age; duration of diabetes; systolic blood pressure; the hypertension rate; the use of hypertension drugs, ACEI /ARB, statins; CHD risk; fatal CHD risk; stroke risk; and fatal stroke risk were significantly higher in the PAD group than in the non-PAD group (P < 0.05 for all). Logistic stepwise regression analysis indicated that ABI was an independent predictor of 10-year CHD and stroke risks in T2DM patients. Compared with those in the T2DM non-PAD group, the odds ratios (ORs) for CHD and stroke risk were 3.6 (95% confidence interval (CI), 2.2–6.0; P < 0.001 ) and 6.9 (95% CI, 4.0–11.8; P < 0.001 ) in those with lower extremity PAD, respectively. In conclusion, lower extremity PAD increased coronary heart disease and stroke risks in T2DM.